2016
DOI: 10.15344/2456-8171/2016/114
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotic Lactic Acid Bacteria on the Characteristics of Galotyri Cheese

Abstract: This study evaluated the effect of probiotic bacteria on the characteristics of the traditional Greek Galotyri cheese. Four Galotyri cheeses were made with the mesophilic starter culture BT002 along with the probiotic strains Lactobacillus acidophilus NCFM, Lactobacillus acidophilus 145, Lactobacillus paracasei subsp. paracasei LbC 81 or Lactobacillus rhamnosus LC 705 and a cheese was also made without the addition of probiotics. The microbiological, physicochemical, aromatic and sensory characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The results in Table 3 present the physicochemical characteristics of white cheese made with and without starter culture. All physicochemical characteristics were not significantly (P>0.05) affected by starter culture addition and this result agrees with that of Evangelia et al [27] who reported that the starter culture addition in cheese showed no significant variation in the composition. The result of fat content is in agreement with Salih and Abdalla [10] who stated that the fat content of cheese was not affected by the starter culture addition and this result might be due to a minor contribution of lactic acid bacteria to the lipolysis process in fermented dairy products [4].…”
Section: Effect Of Starter Culture On the Physicochemical Characteristics Of Cheesesupporting
confidence: 91%
“…The results in Table 3 present the physicochemical characteristics of white cheese made with and without starter culture. All physicochemical characteristics were not significantly (P>0.05) affected by starter culture addition and this result agrees with that of Evangelia et al [27] who reported that the starter culture addition in cheese showed no significant variation in the composition. The result of fat content is in agreement with Salih and Abdalla [10] who stated that the fat content of cheese was not affected by the starter culture addition and this result might be due to a minor contribution of lactic acid bacteria to the lipolysis process in fermented dairy products [4].…”
Section: Effect Of Starter Culture On the Physicochemical Characteristics Of Cheesesupporting
confidence: 91%
“…The differences between the acetaldehyde levels of the cheeses were statistically significant (P <0.05). Evangelia et al, (2016) detected the presence of acetaldehyde in Galotyri cheese.…”
Section: Aldehydesmentioning
confidence: 97%
“…Acetaldehyde, which gives green apples, walnuts and roasted odors to foods, is an important volatile compound for the aroma formation of dairy products such as yogurt, fermented milk and fresh cheeses (Evangelia et al, 2016). Acetaldehyde is commonly found in fermented milk products and has a distinctive sweet and pungent odor.…”
Section: Aldehydesmentioning
confidence: 99%
“…The decrease in the count of probiotic bacteria in the cheese matrix during the ripening period has been obtained in similar studies as well. It has been stated that the main reason for this was associated with the increase in saline concentration in the cheese matrix during the ripening period (Castro et al, 2015;Evangelia et al, 2016;Moraes et al, 2018).…”
Section: Viability Of Lactobacillus Paracasei Used As Probiotic In Cheese During the Ripening Periodmentioning
confidence: 99%